Can AI Improve Patient Safety? An Academic Perspective on Digital Health's Promise and Perils - Rasit Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Can AI Improve Patient Safety? An Academic Perspective on Digital Health's Promise and Perils The integration of Artificial Intelligence (AI) into healt...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Patient Care